Dynamics and Control of Advanced Structures and Machines Contributions from the 3rd International Workshop, Perm, Russia - Matveenko, Valerii P.; Krommer, Michael; Belyaev, Alexander K.; Irschik, Hans (Springer International Publishing : Imprint: Springer, 2019)
The volume includes 30 contributions from the 3rd International Workshop on Advanced Dynamics and Model Based Control of Structures and Machines representing the frontiers in the mechanics of controlled machines and structures. The Workshop, held in Perm, Russia in September 2017 continued a series of international workshops, starting in with the Japan - Austria Joint Workshop on Mechanics and Model Based Control of Smart Materials and Structures, the Russia - Austria Joint Workshop on Advanced Dynamics and Model Based Control of Structures and Machines and the first two editions of the International Workshop on Advanced Dynamics and Model Based Control of Structures and Machines. The previous workshops took place in Linz, Austria in September 2008 and April 2010, in St. Petersburg, Russia in July 2012 and in Vienna, Austria in September 2015. The up-to-date contributions are authored by internationally re-known leading experts in dynamics and control representing a broad spectrum of topics in the field of Advanced Structures and Machines; both, with respect to theoretical aspects as well as applications to contemporary engineering problems.